The Child Focused Injury Risk Screening Tool (ChildFIRST) for 8-12-year-old Children: A Validation Study Using A Modified Delphi Method. Issue 3 (2nd July 2020) - Jimenez-Garcia, John Alexander; Hong, Chang Ki; Miller, Matthew B.; DeMont, Richard
ABSTRACT: The purpose of this Delphi-study was to establish the face and content validity of 10 movement skills, each with four evaluation criteria, to create the Children Focused Injury Risk Screening Tool (ChildFIRST) for 8–12-year-old children. We asked an international expert panel (n = 22) to validate a series of movement skills and evaluation criteria. This Delphi-process consisted of three rounds. In the first two rounds, the experts scored the movement skills and evaluation criteria using 5-point Likert scales. Consensus on validating an item was achieved when 75% or more of the experts scored "Agree" or "Strongly Agree." In the third-round, the experts ranked and established the final list with the validated movement skills and evaluation criteria. This study provided preliminary validity evidence for 10 movement skills, each with four evaluation criteria, to create the ChildFIRST. The ChildFIRST is designed to be used to evaluate movement competence and risk of musculoskeletal injury.